LIPI COREMAP-CTI Nusa Manggala oceanographic survey, I: oceanic mesozooplankton community from epipelagic zones of North-Eastern part of the Indonesian waters -adjacent to the Southwest Pacific Ocean. Issue 1 (September 2020) - Lukman, M; Fitriya, N; Prayitno, H; Afdal, A; Nasir, A; Kaisupi, T; Avianto, P; Hernawan, U E
Abstract: During the Indonesia LIPI COREMAP CTI oceanographic survey of RV. Baruna Jaya VIII, at the end of 2018 to the outermost small Islands of the north-eastern part of Indonesia, the mesozooplanktonic community were studied for their structure and distribution along the epipelagic zone of the waters influenced by the movement of the southwest Pacific Oceans water masses. This study aimed at exploring the oceanographic condition of the trophic level of the water's masses during the end of the dry season in Indonesia. A total of 42 taxonomic groups of mesozooplankton were identified, including general fish larvae and eggs. Calanoida and cyclopoid Copepoda dominated (up to 69%) the structure of all survey points. The composition slightly varied across the survey sites, with the abundance of all groups ranged from 24 to 167 ind. per m 3 . While the main current follows a pattern of the southwest Pacific Ocean, the planktonic community might highlight the condition of the Ocean.